Struktur, Kinerja, Dan Kluster Industri Rokok Kretek: Indonesia, 1996-1999 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT This paper attempts to illuminate the dynamics of Indonesia's clove cigarette industry using Structure-Conduct-Performance (SCP) paradigm and industrial cluster approach We employed concentration ratios (CR4, CR8, and 11111) and performance ratios in SCP analysis. To identift industrial clusters, we used Geographic Information System (GIS) and some tools of analysis, mainly size and specialization index. The structure of clove cigarette industry suggested that an oligopoly with high concentration has been found, albeit declined slightly over the period 1996-1999. As far as geographic concentration is concerned, we found that this industy has clustered overwhelmingly in and around Kudus, Kediri. Surabaya. and Malang.